Calcium-dependent depolarizations originating in lizard motor nerve terminals - Morita, K (J Neurosci, 1989)
Action potentials and afterpotentials were recorded via a microelectrode inserted into motor axons innervating the lizard ceratomandibularis muscle. Intra-axonal injection of Lucifer yellow dye indicated that these axons innervate multiple (at least 6–25) motor terminals. In 10 mM tetraethylammonium (TEA), the action potential was followed by a sequence of afterpotentials, whose amplitude and duration increased with increasing proximity to motor nerve terminals. In axons impaled within 1 mm of their most distal terminals, these afterpotentials included a depolarizing plateau (mean amplitude and duration: 32 mV, 24 msec) and a subsequent smaller depolarization that decayed over a time course of several hundred milliseconds. These depolarizing afterpotentials were Ca dependent: They increased with increasing bath [Ca] and were abolished by low [Ca]-high [Mg] solutions, by omega-conotoxin (GVIA, 1 microM), by addition of Cd (1 microM) or Mn (0.3–1 mM) to the bath, and by selective perfusion of Cd over the terminal region. In [Ca]-free solutions the afterpotentials were restored by selective perfusion of Ca over the terminal region but not by Ca applied to the more proximal nerve trunk. When Na influx was eliminated by 1–10 microM tetrodotoxin or by substitution of TEA for bath Na, passage of depolarizing current into the axon evoked prolonged depolarizing afterpotentials that were blocked by Mn. Bay K 8644 (0.1–1 microM), a dihydropyridine that prolongs the opening of certain calcium channels, enhanced mainly the slower component of the depolarizing afterpotential. Nimodipine (0.1–1 microM), a dihydropyridine that favors the closed state of some calcium channels, shortened the plateau phase of the depolarizing afterpotential. Another antagonist dihydropyridine, nitrendipine (0.1–1 microM), had little or no effect on the depolarizing afterpotential but did antagonize the actions of Bay K 8644. These results suggest that the intraaxonally recorded Ca- dependent afterpotentials are caused by electrotonic spread of depolarizations produced by calcium influx into that axon's terminals and that some motor nerve terminal calcium channels are sensitive to certain dihydropyridines.